Mycorrhizal Association Better Predicts Tree Effects on Soil Than Leaf Habit - Midgley, Meghan G.; Sims, Rachel S. (Frontiers in Forests and Global Change, 2020)
Predicting the ecological consequences of shifting forest composition requires an understanding of how tree species alter the soils beneath them. However, given the huge number of tree species on earth, it is critical to assess the extent to which easily observable traits facilitate the prediction of soil biogeochemistry. Both aboveground and belowground traits are important drivers of forest function. The objective of this study was to assess the relative importance of leaf habit (evergreen or deciduous) and root mycorrhizal association (arbuscular [AM] or ectomycorrhizal ECM]) on biogeochemistry. The relative importance of these two traits for carbon (C) and nitrogen (N) dynamics have proven difficult to disentangle as most deciduous tree species associate with AM fungi and most evergreen tree species associate with ECM fungi. Using planted, single-species forestry plots at The Morton Arboretum (DuPage County, IL), we found that mycorrhizal association better predicted tree effects on soil than leaf habit. While both leaf habit and mycorrhizal association drove variation in soil C:N ratios, mycorrhizal association alone predicted differences in soil pH, available N pools, extracellular enzyme activities, and C and N cycling rates. Surprisingly, ammonium concentrations were higher and net nitrification rates were faster in ECM plots than in AM plots. Greater N-degrading enzyme activities in ECM plots and intrinsically high soil pH across the garden likely drove more rapid N cycling in ECM plots. Overall, this study supports the inclusion of mycorrhizal association in terrestrial biosphere models, but suggests that the effects of mycorrhizal association on N dynamics may be site-dependent.